Morphological and phylogenetic evidence for recognition of a new species of Kirschsteiniothelia, K. agumbensis and validation of five new combinations in Kirschsteiniotheliaceae - P. Sruthi, Onden; Rajeshkumar, Kunhiraman C.; M. Gowrav, Shivapura; A. Ansil, Parayelil; K. Ashtamoorthy, Sreejith (Phytotaxa, 2024)
This study introduces a new species of Kirschsteiniothelia from Agumbe in the central Western Ghats of Karnataka, India. This new species differs from the allied species by its reduced to sessile conidiophores and cylindrical, straight to flexuous, coarsely verrucose to granulate to punctate, 18–41 euseptate elongated conidia. Phylogenetic analyses of combined ITS, LSU and SSU sequence data delineated K. agumbensis as a new lineage allied to Kirschsteiniothelia rostrata under the family Kirschsteiniotheliaceae. Furthermore, pairwise homoplasy index of phylogenetically closely related taxa also confirmed it as a new species.